Sobre Iván Olaya Peláez, Pilar González Bernaldo de Quirós, Jorge Márquez Valderrama (eds. académicos), Raza, eugenesia y políticas públicas en América Latina, 1900-1950 - Agostoni, Claudia (Historia Mexicana, 2025)
-